(untitled) (LEARNing Landscapes, 2011)
A new approach to researching childhood experience has become established whereby researchers are seeking out ways of giving voice to children and young people by "close listening" and engaging them in the research process. In this way, researchers can choose to adopt a childlike perspective, to recognize and pay due attention to children’s multiple ways of "seeing" childhood in particular and the world in general.Visual research is well placed to access,interpret,and give voice to children’s worlds. This is achieved by adopting child-sensitive research methods and by recognizing that children’s experience and agency are important and worthy of study.